Effect of different feeding programs employing supplemental colostrum on serum total protein and albumin, and performance of newborn calves (Scientia Agricola, 1994)
The serum total protein and albumin concentrations and the performance under different milk feeding programs were evaluated in twenty-four female Holstein newborn calves, randomly allocated in three treatments. The animals were daily fed milk or supplemental colostrum, in different feeding programs during the first thirty days of Ufe. Blood samples were collected at 3; 5;10; 15; 17; 20; 22; 25; 30; 40; 50 and 60 days of age and analysed for serum total protein and serum albumin. Animals were weighed at 0; 5; 10; 15; 20; 25; 30; 40; 50 and 60 days after birth. In the first sixty days, the serum total protein concentration in treatment 3 (colostrum fed twice a day) was higher (p < 0.05) than in treatment 1 (milk). The concentration of serum was also different at different ages (p < 0.0001). During the experimental period the total protein decreased (equation r² = 0.98). Serum albumin levels were similar at all ages, but different in treatments. Treatment 2 (colostrum fed once a day) levels were higher (p < 0.05) than in treatment 1 for serum albumin. Treatment 3 body weight gain was higher (p < 0.05) than in treatment 1 during the experimental period. It was concluded that the best performance was found in calves that received a supplemental colostrum diet twice a day.